Downregulation of NCOA4 expression indicates poor prognosis and promotes the progression of cholangiocarcinoma - Wenlong Shen; Yi Liu; Bing Dai; Changling Qin; Yongli Fu; Xi Li; Chi Liu (PLoS ONE, 2025)
The aim of this study was to investigate how the cholangiocarcinoma cell lines RBE and HCCC-9810 responded to NCOA4 downregulation in terms of proliferation, migration and invasive.First,we analyzed the differential expression and survival prognosis of the NCOA4 gene using a bioinformatic approach,as well as validation using clinical samples.Next,cholangiocarcinoma cells were cultured and the NCOA4 gene was down-regulated with siRNA,and then NCOA4 and GPX4 expression was detected using qPCR and Western blot.Cell was measured using CCK8, cell cloning, wound healing, and transwell migration and invasion.Levels of changes in indicators related to ferroptosis were measured after induction of iron metamorphosis by Erastin. Data from TCGA showed that NCOA4 shows greater downgrade in tumor tissues than in non-tumor tissues and the overall survival (OS) of patients with low NCOA4 expression was significantly shorter than that of patients with high NCOA4 expression.The qPCR results showed that NCOA4 was expressed at low levels in cholangiocarcinoma tissue specimens; the mRNA expression of NCOA4 decreased after knocking down NCOA4 in cells. Western blot (WB) analysis showed that NCOA4 downregulation led to an increase in GPX4 expression. The cell cloning assay confirmed that downregulation of NCOA4 significantly increased cell viability. The transwell and wound healing assays demonstrated that the proliferation rate increased after downregulation of NCOA4. After NCOA4 silencing, ferroptosis indicators such as Fe2+, MDA, and ROS expression were lowered;GSH expression was increased.Our findings indicated the regulatory effects of NCOA4 on GPX4 protein and its contribution to malignant progression in CCA, which could provide a potential therapeutic target for CCA.